2012
DOI: 10.3748/wjg.v18.i41.5839
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids for the treatment of non-alcoholic fatty liver disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) has been recognized as a major health burden. It is the most important cause of chronic liver disease and a major independent cardiovascular risk factor. Lacking a definite treatment for NAFLD, a specific diet and an increase in physical activity represent the most commonly used therapeutic approaches. In this review, major literature data about the use of omega-3 polyunsaturated fatty acids (n-3 PUFAs) as a potential treatment of NAFLD have been described. n-3 PUFAs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
97
0
15

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(119 citation statements)
references
References 81 publications
7
97
0
15
Order By: Relevance
“…PUFA act by regulating gene transcription factors involved in hepatic lipid metabolism [52] which have down-stream effects of increased insulin sensitivity, inhibition of hepatic lipogenesis, increased fatty acid oxidation and reduction of pro-inflammatory cytokines [53]. Various studies using a range of PUFA dosages, composition of the PUFA and duration of treatment have not found consistent results in the context of NAFLD Table 4 [53]. More importantly, most of the studies did not evaluate histological endpoints of treatment.…”
Section: Thiazolidinedionesmentioning
confidence: 98%
See 2 more Smart Citations
“…PUFA act by regulating gene transcription factors involved in hepatic lipid metabolism [52] which have down-stream effects of increased insulin sensitivity, inhibition of hepatic lipogenesis, increased fatty acid oxidation and reduction of pro-inflammatory cytokines [53]. Various studies using a range of PUFA dosages, composition of the PUFA and duration of treatment have not found consistent results in the context of NAFLD Table 4 [53]. More importantly, most of the studies did not evaluate histological endpoints of treatment.…”
Section: Thiazolidinedionesmentioning
confidence: 98%
“…Among the first trials, Capanni et al found that PUFA improved liver aminotransaminases, metabolic profiles and hepatic steatosis on imaging [54]. Other studies have provided collaborative observations [53]. A meta-analysis of 9 trials and 355 patients found that there were beneficial changes in hepatic steatosis but less convincing evidence of improvement in aminotransaminases with PUFA therapy [55].…”
Section: Thiazolidinedionesmentioning
confidence: 99%
See 1 more Smart Citation
“…It facilitates the influx of free fatty acids from the adipose tissue into the liver, hepatic oxidative stress, cytokine production, reduced VLDL secretion, and the growth of the intestinal microbiome [43]. Unhealthy diet and a sedentary lifestyle can alter the stability of the intestinal microbiome composition.…”
Section: Weta Et Almentioning
confidence: 99%
“…Aquaculture (salmon and trout) accounted for over 70 % of the consumption of oil in 2011 primarily in Chile and Peru. However, direct human consumption of fish oil has been increasing over the past 5 years, due to marketer's influence and due to an increase in awareness of health benefits of long-chain (LC) n-3 PUFA, such as prevention of type-2 diabetes (Asian, Eskimos), prevention of insulin-resistance (3,4) , decrease in plasma TAG (5) , anti-inflammatory effect (6) , the defect of brain and retina development (only if deficiency in LC n-3 PUFA), primary cardiovascular prevention (5) , anti-stress and anti-adrenergic effect (7,8) and decrease in liver steatosis (9) . Because of these health benefits and of some deleterious effects of deficiency, many national and international recommendations have been proposed about the optimal intake of LC n-3 PUFA for the general population.…”
mentioning
confidence: 99%